2021
DOI: 10.20525/ijrbs.v10i7.1470
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ self-efficacy and work performance of employees as mediated by work environment

Abstract: The study aimed to determine the correlation between self-efficacy and work performance as mediated by the work environment. To support the theory of study, literature was reviewed. The study used the descriptive correlational research design and to gather the data, questionnaires were used. The population of the study was all the faculty and employees of the Divine Word Colleges in the Ilocos Region, Philippines. The study found that their self-efficacy is high and it affects the work performance specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…The employees will undoubtedly accept defeat in demoralizing situations at the workplace, diminishing their job performance. More recent researches have indicated that employees with greater self-efficacy attain more incredible job performance than employees with lesser self-efficacy (Abun et al, 2021;Judge & Bono, 2001;Judge et al, 2007;Stajkovic & Luthans, 1998;Tims et al, 2014). Contrarily, elucidate that employees' creativity and not self-efficacy shape employees' job performance.…”
Section: Relationship Between Self-efficacy and Job Performancementioning
confidence: 95%
See 4 more Smart Citations
“…The employees will undoubtedly accept defeat in demoralizing situations at the workplace, diminishing their job performance. More recent researches have indicated that employees with greater self-efficacy attain more incredible job performance than employees with lesser self-efficacy (Abun et al, 2021;Judge & Bono, 2001;Judge et al, 2007;Stajkovic & Luthans, 1998;Tims et al, 2014). Contrarily, elucidate that employees' creativity and not self-efficacy shape employees' job performance.…”
Section: Relationship Between Self-efficacy and Job Performancementioning
confidence: 95%
“…Employees' self-efficacy can be associated with their job performance based on research conducted by (Abun et al, 2021). Several researchers have related self-efficacy to various other factors which lead to job performance.…”
Section: Relationship Between Self-efficacy and Job Performancementioning
confidence: 99%
See 3 more Smart Citations